Tasks and Rubrics for Assessing Research Skills of Undergraduate Students - Nasrudin, Dindin; Dirgantara, Yudi; Suhendi, Herni Yuniarti (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
Intraarticular learning can improve students' research skills, one of which is strengthening educational seminar courses. This research aims to develop a task and rubric to assess undergraduate students' research skills. This study is a research and development using the DDD-E model design (Decide, Design, Development, and Evaluation). This research has succeeded in compiling a task and rubric to measure undergraduate students' research skills in preparing research proposals. This rubric can be implemented by researchers in the broader area with some adjustments.